2021
DOI: 10.1089/neur.2021.0050
|View full text |Cite
|
Sign up to set email alerts
|

In-Season Concussion Symptom Reporting in Male and Female Collegiate Rugby Athletes

Abstract: Symptom inventories are generally only collected after a suspected concussion, but regular in-season monitoring may allude to clinical symptoms associated with repetitive subconcussive impacts and potential undiagnosed concussions. Despite sex-specific differences in symptom presentation and outcome of concussion, no return-to-play protocol takes sex into account. The objective of this study was to monitor a cohort of contact-sport athletes and compare the frequency and severity of in-season concussion-like sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The overall differences in reporting by sex are not surprising as generally female athletes will report more symptoms after a concussion. 18,19,41 Clinically, these findings are important as female athletes may over-report at baseline or male athletes may under-report. This stresses the importance of using a change score when determining a concussion diagnosis while using the VOMS regardless of modality.…”
Section: Discussionmentioning
confidence: 99%
“…The overall differences in reporting by sex are not surprising as generally female athletes will report more symptoms after a concussion. 18,19,41 Clinically, these findings are important as female athletes may over-report at baseline or male athletes may under-report. This stresses the importance of using a change score when determining a concussion diagnosis while using the VOMS regardless of modality.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation has indicated that clinical concussion assessments may be subject to sampling bias, as current assessments have been constructed around studies involving mostly male participants. (Gessel et al, 2007;Granito, 2002;Kieffer et al, 2021;Mihalik et al, 2009;O'Connor et al, 2017;Schatz et al, 2011;Wallace et al, 2017;Zuckerman et al, 2014). Therefore, generalizing head-injury and concussion assessment tools developed in males to the female athlete population is likely to present imprecise results.…”
Section: Introductionmentioning
confidence: 99%